GENETIC EVALUATION BIRTH WEIGHT AND WEANING WEIGHT OF GARUT SHEEP IN UPTD-BPPTD MARGAWATI GARUT - Ai Nurfaridah (Program Studi Peternakan, Universitas Padjadjaran PSDKU Pangandaran, 2022)
This research was conducted at Unit Pelaksana Teknis Daerah Balai Pengembangan Perbibitan Ternak Domba (UPTD BPPTD) Margawati Garut on February 2014. The aim of this research was to evaluate Garut sheep genetic trait with description genetic parameter is heritability and breeding value birth weight and weaning weight of Garut Sheep in UPTD-BPPTD Margawati Garut. Data collection technique is purposive sampling. Data collected were 4128 records from 1650 dams, 78 sires, and 2064 Garut sheep, during 2005 to 2013. Variety components and the heritability value were suspected by Restricted Maximum Likelihood (REML) method used Animal Model pattern of direct additive genetic effect, maternal genetic effect and permanent environmant and Breeding Value estimated byBest Linier Unbiased Prediction (BLUP). Fix effect were used sex and birth type. The result of this research was heritability value of birth weight and weaning weight with direct additve genetic effect was 0.33 and 0.32 included in large category, with maternal genetic effect was 0.26 and 0.28 included in medium category. the maternal genetic value with same trait 0.12 and 0.57.heritability birth weigt and weaning weight for permanent environment was 0.23 and 0.25 wit permanent environment value 0.32 and 0.35 included in medium category. Estimated Breeding value for the three best ID number 3680, 1496, and 1138